Effects of ascorbic acid on impaired vascular reactivity in aortas isolated from age-matched hypertensive and diabetic rats - Ajay, M.; Mustafa, Mohd Rais (Elsevier, 2006)
Impaired vascular reactivity is a hallmark of several cardiovascular diseases that include hypertension and diabetes. This study compared the changes in vascular reactivity in age-matched experimental hypertension and diabetes, and, subsequently, tested whether these changes could be affected directly by ascorbic acid (10 μM). Endothelium-derived nitric oxide (NO) modulation of ascorbic acid effects was also investigated. All the experiments were performed in the presence of a cyclooxygenase inhibitor, indomethacin (10 μM). Results showed that the endotheliumdependent and -independent relaxations induced by acetylcholine (ACh) and sodium nitroprusside (SNP), respectively, were blunted to a similar extent in isolated aortic rings from age-matched spontaneously hypertensive (SHR) (Rmax: ACh = 72.83 ± 1.86%, SNP = 96.6 ± 1.90%) and diabetic(Rmax: ACh = 64.09 ± 5.14%, SNP = 95.84 ± 1.41%) rats compared with aortic rings of normal rats (Rmax : ACh = 89%, SNP = 104.0 ± 1.0%). The α1 - receptor-mediated contractions induced by phenylephrine (PE) were augmented in diabetic (Cmax = 148.8 ± 9.0%) rat aortic rings compared to both normal (Cmax = 127 ± 6.9%) and SHR (Cmax = 118 ± 4.5%) aortic rings. Ascorbic acid pretreatment was without any significant effects on the vascular responses to ACh, SNP and PE in aortic rings from normal rats. Ascorbic acid significantly improved ACh-induced relaxations in SHR (Rmax = 89.09 ± 2.82%) aortic rings to a level similar to that observed in normal aortic rings, but this enhancement in ACh-induced relaxations was only partial in diabetic aortic rings. Ascorbic acid lacked any effects on SNP-induced relaxations in both SHR and diabetic aortic rings. Ascorbic acid markedly attenuated contractions induced by PE in aortic rings from both SHR (Cmax = 92.9 ± 6.68%) and diabetic (Cmax = 116.9 ± 9.4%) rats. Additionally, following inhibition of nitric oxide synthesis with L-NAME, ascorbic acid attenuated PE-induced contractions in all aortic ring types mstudied. These results suggest that (1) vascular hyper-responsiveness to α1-receptor agonists in diabetic arteries is independent of endothelial nitric oxide dysfunction; (2) ascorbic acid directly modulates contractile responses of hypertensive and diabetic rat aortas, likely through mechanisms in mpart independent of preservation of endothelium-derived nitric oxide.